Phylogenetic analysis of the first four SARS‐CoV‐2 cases in Chile. Issue 9 (8th April 2020) - Castillo, Andrés E.; Parra, Bárbara; Tapia, Paz; Acevedo, Alejandra; Lagos, Jaime; Andrade, Winston; Arata, Loredana; Leal, Gabriel; Barra, Gisselle; Tambley, Carolina; Tognarelli, Javier; Bustos, Patricia; et al.
Abstract: The current pandemic caused by the new coronavirus is a worldwide public health concern. To aboard this emergency, and like never before, scientific groups around the world have been working in a fast and coordinated way to get the maximum of information about this virus when it has been almost 3 months since the first cases were detected in Wuhan province in China. The complete genome sequences of around 450 isolates are available, and studies about similarities and differences among them and with the close related viruses that caused similar epidemics in this century. In this work, we studied the complete genome of the first four cases of the new coronavirus disease in Chile, from patients who traveled to Europe and Southeast Asia. Our findings reveal at least two different viral variants entries to Chilean territory, coming from Europe and Asia. We also sub‐classified the isolates into variants according to punctual mutations in the genome. Our work contributes to global information about transmission dynamics and the importance to take control measures to stop the spread of the infection. Highlights: First genetic study of the SARS‐CoV‐2 isolates in Chile. At least two different viral variants were identified from Chilean travelers. S and G Chilean variants are associated to European and Asian viral isolates.